Retinal microglia signaling affects Müller cell behavior in the zebrafish following laser injury induction. Issue 6 (22nd February 2019) - Conedera, Federica Maria; Pousa, Ana Maria Quintela; Mercader, Nadia; Tschopp, Markus; Enzmann, Volker
Abstract: Microglia are the resident tissue macrophages of the central nervous system including the retina. Under pathophysiological conditions, microglia can signal to Müller cells, the major glial component of the retina, affecting their morphological, molecular, and functional responses. Microglia–Müller cell interactions appear to be bidirectional shaping the overall injury response in the retina. Hence, microglia and Müller cell responses to disease and injury have been ascribed both positive and negative outcomes. However, Müller cell reactivity and survival in the absence of immune cells after injury have not been investigated in detail in adult zebrafish. Here, we develop a model of focal retinal injury combined with pharmacological treatments for immune cell depletion in zebrafish. The retinal injury was induced by a diode laser to damage photoreceptors. Two pharmacological treatments were used to deplete either macrophage–microglia (PLX3397) or selectively eliminate peripheral macrophages (clodronate liposomes). We show that PLX3397 treatment hinders retinal regeneration in zebrafish, which is reversed by microglial repopulation. On the other hand, selective macrophage elimination did not affect the kinetics of retinal regeneration. The absence of retinal microglia and macrophages leads to dysregulated Müller cell behavior. In the untreated fish, Müller cells react after injury induction showing glial fibrillary acidic protein (GFAP), Phospho‐p44/42 MAPK (Erk1/2), and PCNA upregulation. However, in the immunosuppressed animals, GFAP and phospho‐p44/42 MAPK (Erk1/2) expression was not upregulated overtime and the reentry in the cell cycle was not affected. Thus, microglia and Müller cell signaling is pivotal to unlock the regenerative potential of Müller cells in order to repair the damaged retina. Main Points: Immune cell depletion hampers the regenerative capacity of zebrafish. Retinal regeneration in zebrafish depends on microglia but not peripheral macrophages. Altered DNA damage response (DDR) limits the regenerative potential of Müller glia.